Illuminating Legacy: Tracking the Utilization Pattern of Winter Olympic Venues via Nighttime Light Data - Siyi Yu; Xizhi Zhao; Jinlong Ma; Yujian Liu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
The Winter Olympic Games stimulate significant infrastructure development, yet post-Games venue utilization remains a pressing challenge. Traditional survey-based assessments are often resource-intensive and lack the capacity for continuous, large-scale monitoring. This study employs nighttime light (NTL) remote sensing data to analyze 209 Winter Olympic Game venues, utilizing time series analysis, change point detection, and seasonal decomposition. Results indicate that 32.06% of venues exhibit a significant increase in activity, while 12.92% experience a decline significantly. Two distinct utilization patterns emerge: outdoor sports venues for pre-2000 Games are more likely to face post-Games underutilization due to geographic isolation and high maintenance costs, whereas urban indoor venues can sustain long-term use through multipurpose adaptability and accessibility. The findings confirm NTL data as an effective real-time monitoring tool, supporting data-driven legacy planning. This study highlights the significance of multipurpose design, tourism integration, and policy-driven repurpose in ensuring the long-term sustainability of Olympic infrastructure investments.